Membumikan Tradisi Pesantren di Masyarakat: Relevansi Efektifitas Sorogan Al-Qur’an terhadap Perubahan Sosial di Desa Banjarejo Lampung Timur - Muhammad Nur Amin (Bulletin of Indonesian Islamic Studies, 2023)
The purpose of this study is to describe the form of grounding the pesantren tradition in society through the Qur’an’s sorogan, and to identify the obstacles and relevance of the effectiveness of the Qur’an sorogan to social change in the village of Banjarejo, East Lampung. The author uses qualitative research and social construction theory as an analytical tool. Informants in this study were chosen using the purposive sampling technique. The result of this paper is that the relevance of the effectiveness of the Qur’an sorogan to social change in society can be found in the emergence of a moderate attitude, both in 'ubūdiyyah and khulūqiyyah wa mu'āmalah ways. The implementation of this Qur’an sorogan: First, begins with an ustad listening to the recitation of the Qur'an by senior students one by one. The tutor slowly corrects the recitation if some tajwid errors are found. Second, Qur'an teachers explained little about the understanding of verses by various existing aspects. In particular, the above can increase societal scientific values and create a moderate attitude amid existing differences. In this matter, tutors encounter unavoidable obstacles while improving senior students' reading due to age factors and various character backgrounds.